Nickel hydroxide nanosheet membranes with fast water and organics transport for molecular separation. Issue 43 (24th October 2016) - Qu, Yan; Zhang, Qiu Gen; Soyekwo, Faizal; Gao, Run Sheng; Lv, Rui Xue; Lin, Chen Xiao; Chen, Meng Meng; Zhu, Ai Mei; Liu, Qing Lin
Abstract : Nickel hydroxide nanosheet membranes are facilely prepared for water purification and organic solvent nanofiltration with ultra-high fluxes. Abstract : Two-dimensional nanosheets of late show great promise as novel materials for size-selective separation membranes of high efficiency. Herein, we demonstrate a novel laminated nanofiltration membrane for fast water purification and organic solvent nanofiltration using the 1 nm-thick and 50 nm-wide nickel hydroxide nanosheets that are facilely prepared by a green chemistry method. The resulting membranes exhibit uniform and flectional two-dimensional laminated structure. With about 1 nm high laminated channels, they allow super-fast transport of water and organic solvents. The water and organic fluxes are three orders of magnitude higher than commercially available polymeric nanofiltration membranes. In addition, the membranes have high retention for organic dyes in aqueous and organic solutions. Typically, the 3.18 μm-thick membrane with the molecular weight cut-off of 328 g mol −1 has an outstanding pure water flux of 99 L m −2 h −1 bar −1 and up to 97% rejection for direct yellow dye molecules. The newly developed nickel hydroxide nanosheets and the subsequent membranes have great potential application in water purification, organic solvent filtration and electronic devices.